Thank you for the opportunity to help you with your question!

This Question is currently still in progress and will be
finished shortly

Please find the solution enclosed here with. In case of any doubt please feel free to ask … If you need help in any assignment of math/ science … any online exam / discussion, Please contact for quick & quality services.

Jul 14th, 2015

P(x) = −x^{3} + x^{2} + 12x

to find factors equate P(x) = 0 hence write

−x^{3} + x^{2} + 12x = 0

substituting x = 0 we get P(x) = 0 hence x = 0 is a factor of the given polynomial

take out x from all the terms we get ,x (−x^{2} + x^{} + 12) =0

we can rearrange it as ; x (−x^{2} + 4x-3x + 12) =0 ; x { -x(x^{} -4) -3(x -4)} =0

Now (x-4) is common hence we can take it out and get